Strategi Pengelolaan Air Terjun Peng Empu Sebagai Daya Tarik Wisata Alam di Desa Cau Belayu, Kecamatan Marga, Kabupaten Tabanan - Diantasari, Ni Luh Putu Mita Dewi; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
The research of management strategy of Peng Empu Waterfall tourism attraction held in Cau Belayu Village, Marga District, Tabanan Regency. The objective of this research is to know the perception of community and tourist about the management Peng Empu Waterfall tourism attraction and to know the management then been analized with SWOT. The data that used on this research are the general condition of Cau Belayu Village, the potensial of Peng Empu Waterfall. Data collecting technique done by observation, interview, and bibliography study. Peng Empu Waterfall tourism object have potential attraction to attractive tourist enthusiasm. There are a waterfall with 25 meters height approximately. That caused the surrounding of waterfall is cool and fresh, beside of that the panorama around waterfall like unifilation of natural forest and a long of pathway there are a lot of plantation of the community that coolies along of the pathway to the waterfall, so the tourism issue of this period go along direct to “back to nature” issue have big opportunity to get the market from the eco tourism. Due the SWOT there are fundamental problem on the management of Peng Empu Waterfall tourism attraction : the problem of the management object, the problem of the continuation of natural environment, the problem of the human resources, the limited of the information media to the tourist and availability medium supporting tourist at the tourism object. With the approach and the analized, it have determined the vision of the management is the Peng Empu Waterfall tourism attraction still maintain natural preservation and to explore the community. The management vision is to use all the potencies and to keep natural preservation have benefit to increase the local comunity income and also regency income.   Keywords : Management of Strategy, Peng Empu Waterfall